(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
Fossil remains of sirenians (Mammalia; Dugongidae) are reported from the late early Miocene (Burdigalian) Qom Formation near the town of Shirin Su, northwest Kabudar Ahang region, west of Tehran, Iran. The fossils consist of partial postcranial skeletons preserved mostly as natural molds in limestone. In the absence of skulls or other diagnostic elements, it is not evident which dugongid subfamily these specimens represent: Halitheriinae or Dugonginae. Both subfamilies were present in contemporaneous Western Tethys (Mediterranean) deposits, but so far only dugongines have been found in Neogene rocks of Eastern Tethys. Since the Iranian deposits are located between these two parts of the former Tethys Seaway, it will be interesting to see which group(s) the Iranian sirenians prove to represent, once their taxonomic identity has been determined through future discoveries.